Formation of “Red Scare” Concept in USA in First Half of XX Century - Y. A. Levin (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The issue of how the an important and multifaceted aspect of domestic and foreign policy formed by US FBI, called the "Red Scare" is addressed in the article. It is shown that this political and ideological concept seemed unacceptable for distribution in the United States, since it created a danger of the penetration of communist ideas and their adherents into all government bodies and major public organizations. Factors that influenced the strengthening of the FBI’s position in the fight against communist ideology in the United States in the 1920s, in particular, terrorist acts carried out by left-wing forces, which allowed the FBI to implement a program of struggle (Palmer raids) with organizations, adhering to communist views are examined. The measures taken by the FBI and its director John Edgar Hoover in the 1930s against Soviet intelligence, which contributed to reinforcing negative perceptions of the “Red Scare” within the agency are highlighted. The authors conclude that the position of the FBI influenced the building of the attitude of the entire US intelligence community in this vein, which in turn had a great impact on the development of the country’s domestic and foreign policy.